Kajian Psikologi Sastra dan Nilai Karakter Novel “Senja dan Pagi Karya Alffy Rev dan Linka Angelia” - Mutia Alkhaerat; Azis Azis; Hajrah Hajrah (SOCIETIES: Journal of Social Sciences and Humanities, 2022)
Abstract.This study aims to describe the aspects of character needs in the Senja dan Pagi novels by Alffy Rev and Linka Angelia based on Abraham Maslow's humanistic psychology theory, and describe the character values of the Senja dan Pagi novels by Alffy Rev and Linka Angelia. This type of research is a type of descriptive qualitative research. This research was conducted by reading the entire story chapter through the novel Senja dan Pagi by Alffy Rev and Linka Angelia. The focus of this research is aspects of the character's humanistic psychological needs and character values. The data sources of this research are obtained from the novel Senja dan Pagi by Alffy Rev and Linka Angelia in the form of sentences or ideas, ideas and quotes that contain: aspects of the character's humanistic psychological needs and character values. Data collection techniques in this study were carried out with reading, note-taking and documentation techniques. The research instrument consisted of the main instrument, namely the researcher himself and supporting instruments such as highlighter and cellphone for documentation. The results of the study found two things, first, aspects of the humanistic psychological needs of the characters in the novel